Physiochemical and functional evaluation of the first-in-class anti-cancer IgE antibody drug, MOv18, through process development and good manufacturing practice production - Heather J Bax; Jitesh Chauhan; Alexandra J McCraw; Melanie Grandits; Chara Stavraka; Heike Lentfer; Tim Hillyer; Simon Carroll; Kim Vigor; Chris Selkirk; Mariangela Figini; Jack Cheeseman; et al. (mAbs)
Antibodies used for cancer therapy are monoclonal IgGs, but tumor-targeting IgE antibodies have shown enhanced effector cell potency against cancer in preclinical models. Research-grade recombinant IgE antibodies have been generated and studied for several decades. The recent Phase 1 clinical trial of the first-in-class MOv18 IgE, however, necessitated the inaugural process development and scaled manufacture of a recombinant IgE to clinical quality standards. During the process development and scaled Good Manufacturing Practice production, we demonstrate the retention of glycosylation state, biophysical profile, and functional characteristics of MOv18 IgE, including Fc-mediated mast cell degranulation and tumor cell killing. Assessment of manufacturing parameters shows expected pH, purity, concentration, and stability properties, as well as below threshold levels of known biological manufacturing contaminants. We confirm the suitability of the pipeline described for generating intact, functionally active, clinical-grade material for this novel therapeutic class as an Investigational Medicinal Product (IMP), with comparable characteristics to the original research-grade antibody. Furthermore, we screened patient blood ex vivo for potential type I hypersensitivity reaction to MOv18 IgE, using the basophil activation test, to identify patients not predicted to be hypersensitive to MOv18 IgE administration. This study supports the production of functionally active clinical grade (IMP) recombinant IgE and paves the way for the development of a new therapeutic antibody class for a range of antigenic specificities and disease settings.